Wskaźniki controllingu kosztów w spółkach dystrybucyjnych energii elektrycznej - Rubik, Jolanta (The Ratios of Controlling Costs in Electric Energy Distribution Companies, 2005)
The financial ratios are on of the most important controlling instruments. In the article was presented the proposition of arrangement the cost of controlling ratios for energy distribution enterprises. There was also discussing shortly, the way of including and interpretation presented ratios.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 330-336